2014
DOI: 10.1021/bm5008635
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Toxicological Evaluation of a Chitosan-l-Leucine Conjugate for Pulmonary Drug Delivery Applications

Abstract: Herein are reported the synthesis of a conjugate of chitosan with L-leucine, the preparation of nanoparticles from both chitosan and the conjugate for use in pulmonary drug delivery, and the in vitro evaluation of toxicity and inflammatory effects of both the polymers and their nanoparticles on the bronchial epithelial cell line, BEAS-2B. The nanoparticles, successfully prepared both from chitosan and the conjugate, had a diameter in the range of 10-30 nm. The polymers and their nanoparticles were tested for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 52 publications
1
34
0
1
Order By: Relevance
“…To avoid side reactions and reduce reaction steric hindrance, some spacer molecules are often used in the coupling process (Table 3) (Denora et al, 2016;Petrin et al, 2019). In some cases, to prevent amino acids from self-polymerization in the presence of EDC, the primary amino groups of amino acids will be protected in advance (Muhsin et al, 2014).…”
Section: Introducing Peptides /Amino Acidsmentioning
confidence: 99%
“…To avoid side reactions and reduce reaction steric hindrance, some spacer molecules are often used in the coupling process (Table 3) (Denora et al, 2016;Petrin et al, 2019). In some cases, to prevent amino acids from self-polymerization in the presence of EDC, the primary amino groups of amino acids will be protected in advance (Muhsin et al, 2014).…”
Section: Introducing Peptides /Amino Acidsmentioning
confidence: 99%
“…reported the conjugate to be relatively more toxic and pro-inflammatory than chitosan alone. The authors suggested that the level of toxicity and inflammatory effects can still enable its utilization for pulmonary drug delivery unless intra-lung concentrations are increased beyond that which they reported [77]. However, this was an entirely in vitro study, and one can only assume that the pro-inflammatory effects of the polymer would be increased in vivo this highlights the need for stringent in vivo testing of pharmacokinetics and safety prior to considering inhalation studies in humans, particularly those with already compromised respiratory disease.…”
Section: Current Opinion On the Future Of Inhalable Polymer-drug Conjmentioning
confidence: 95%
“…In one example, chitosan was conjugated to amino acids such as L-leucine to provide a potentially improved pulmonary delivery system for the model drug diltiazem [77]. The diltiazem-chitosan-leucine conjugate showed an initial rapid burst release of drug, which was followed by slower release with approximately 50% of the drug released over 16 days [69].…”
Section: Chitosan-drug Conjugatesmentioning
confidence: 99%
“…[245][246][247][248][249] Biopolymer Drug Conjugate (BDC) Thermally sensitive biopolymer with the potential ability to quickly form insoluble viscous co-acervate at body temperature can be used for this purpose (Figure 18). 250,251 Although some of the biomedical polymer-drug conjugates are approved for clinical trials, they lack photothermal properties and multi-imaging capabilities, impeding them from imaging-guided precision cancer therapy and total cancer arrested development. 252 Thus, researchers introduced a novel all-in-one biopolymer-drug conjugate nanotheranostics, such as that of intracellular pH-sensitive polydopamine-doxorubicin conjugate nanoparticles under a mild situation that are characterized by excellent photothermal attribute, dual stimuli-triggered drug release activity, and about elongated blood circulation time than nonconjugated doxorubicin.…”
Section: Micellementioning
confidence: 99%